PENGARUH KEPEMIMPINAN DEWAN MA’HADIYAH TERHADAP PENINGKATAN KINERJA PEMBIMBING ASRAMA - Abdul Halim; Abd. Wahed; Herfinatun (STIT Al - Ibrohimy Bangkalan, 2023)
There are two problems that are the main study in this research, first, is there an influence of the leadership of the Ma'hadiyah Council on improving the performance of dormitory supervisors. Second, how much influence does the leadership of the Ma'hadiyah Council have on improving the performance of dormitory supervisors? The population of this research is students at the Mambaul Ulum Bata Bata Pamekasan Islamic Boarding School. The results of the research after data analysis show that the r value of work is 0.751 which is greater than the r value of the product moment table. Where at db=28, both at the 5% significance level, the value is 0.374 and at the 1% significance level, the value is 0.478. Thus the value of r work is greater than the r table of product moment at both the 5% significance level and the 1% significance level so that the hypothesis proposed, namely the work hypothesis (Ha) is accepted while the null hypothesis (Ho) is rejected. The leadership of the Ma'hadiyah Council has a big influence on improving the performance of the Girls' Dormitory Supervisors at the Mambaul Ulum Islamic Boarding School Bata-Bata Panaan Palengaan Pamekasan. This is based on the results of data analysis after consulting with the r value interpretation table which states that the work r value is 0.751 in the range of 0.600 to 0.600. 0.800 with high interpretation.